Optimization of Illumination Performance of Trichromatic White Light-Emitting Diode and Characterization of Its Modulation Bandwidth for Communication Applications - Hua Xiao; Xiangtian Xiao; Kai Wang; Rui Wang; Bin Xie; Kin Seng Chiang (IEEE Photonics Journal, 2018)
We study a trichromatic white light-emitting diode (WLED) system that consists of a blue LED covered with layers of red emissive CdSe/ZnS quantum dots (QDs) and yellow emissive YAG:Ce3+ phosphors. With the knowledge of the individual emission spectra of the blue LED, the QDs, and the phosphors, we develop a method of determining the right amounts of QDs and phosphors to optimize the illumination performance of the WLED. The predicted performances of the WLEDs obtained from our method agree well with experimental results. With this method, we are able to produce white light with, for example, a high color-rendering index of 95.4 and an R9 value of 95.0 at a correlated color temperature (CCT) of 3640 K. We also analyze the modulation characteristics of this WLED system for visible light communication (VLC). By combining the frequency responses of the blue LED, the QDs, and the phosphors, we are able to accurately predict the overall frequency responses and the bandwidths of the WLEDs that have various CCTs and, thus, optimize the bandwidth of the WLED. Our approach of optimizing the performance of a WLED, as verified by our measurement data, is simple and general and can facilitate the selection of suitable light-conversion materials for combined illumination and VLC applications.